Biophysical models of persistent connectivity and barriers on the northern Mid-Atlantic Ridge. (October 2020) - Yearsley, J.M.; Salmanidou, D.M.; Carlsson, J.; Burns, D.; Van Dover, C.L.
Abstract: A precautionary approach to protecting biodiversity on mid-ocean ridges, while permitting seabed mining, is to design and implement a network of areas protected from the effects of mining. Such a network should capture representative populations of vent endemic fauna within regions of connectivity and across persistent barriers, but determining where such connectivity and barriers exist is challenging. A promising approach is to use biophysical modeling to infer the spatial scale of dispersal and the positions where breaks in hydrographic connectivity occur. We use results from a deep-sea biophysical model driven by data from the global array of Argo probes for depths of 1000 m to estimate biophysical connectivity among fragmented hydrothermal vent habitats along the Mid-Atlantic Ridge, from the equator northward to the Portuguese Exclusive Economic Zone surrounding the Azores. The spatial scale of dispersal varies along the ridge axis, with median dispersal distances for planktonic larval durations (PLDs) of 75 d ranging from 67 km to 304 km. This scale of dispersal leads to considerable opportunities for connectivity through mid-water dispersal. A stable pattern of five regions of biophysical connectivity was obtained for PLDs of 100 d or more. Connectivity barriers between these regions can persist even when planktonic larval duration extends beyond 200 d. For a 50 d PLD, one connectivity barrier coincides with the region of the genetic hybrid zone for northern and southern vent mussel species at the Broken Spur vent field. Additional barriers suggest potential for genetic differentiation that so far has not been detected for any taxon. The locations of persistent zones of connectivity and barriers to dispersal suggest that there may be multiple biogeographic subunits along the northern Mid-Atlantic Ridge that should be taken into account in planning for effective environmental management of human activities. Highlights: Argo probes from 1000 m are used to estimate biophysical connectivity along the mid-Atlantic ridge. There is considerable opportunity for hydrothermal vent connectivity through mid-water dispersal. Persistent dispersal barriers exist along the northern mid-Atlantic ridge.